FRANCE'S PARTICIPATION IN MAY MEASUREMENT MONTH 2019: THE WHOLE STARTING POINT OF A COLLECTIVE WORK WITHIN THE FRENCH SOCIETY OF HYPERTENSION (SFHTA). (April 2021) - Lopez-Sublet, Marilucy; Halimi, Jean Michel; Bouhanick, Beatrice; Boivin, Jean Marc; Denolle, Thierry; Mourad, Jean Jacques; Vaisse, Bernard; Fauvel, Jean Pierre; Pathak, Atul
Abstract : Objective: May Measurement Month (MMM) is a global awareness campaign against hypertension launched by the International Society of Hypertension and supported by the World Hypertension League. In France, nearly 1 out of 3 people have hypertension, of which a large proportion remains undiagnosed. The aim of this work is to make data collected during MMM 2019 in France available for the global cohort and raise awareness through this screening action. Design and method: Screening was coordinated by each manager of the 7 different participating sites, while following the standardised MMM protocol. SFHTA (in partnership with Omron France) sponsored centres requesting blood pressure monitors, by offering Omron HEM-FL31/M3 Comfort® devices. Results: Baseline data for 818 subjects (including 66 teenagers) are summarized in joint table. Most participants reported having measured their BP at least once in the past year. 22% measured their BP at least a year ago or never. The number of patient with known hypertension was 208 (25.4%), 176 (21.5%) were treated, out of them 101 (57, 4%) were controlled (BP < 140/90 mmHg). In our cohort, 76 healthy subjects (9.2%) had unknown high normal BP and 109 healthy subjects (13.3%) have been screened as new hypertensive patients. Figure. No caption available. Conclusions: Up to day, more than 2.7 million people have taken part in the MMM program worldwide. This first survey in France highlights how a scientific society, such as SFHTA, could beyond education and science also promote a non expensive hypertension screening program to support global awareness and local actions. A wider participation with ancillary studies are planned for 2020 with the need to clarify ethical issues, in order to use national data according to French legislation. Thanks to all patients and the teams at each centre who took part in this campaign.